Impact of TV Commercials on Persuasive Speech: A Critical Review - Begum, Minowara (Journal of NELTA, 2015)
With the growth of global economy, TV commercials not only have added a new dimension to the communication process throughout the world, but also have been widely recognized as authentic materials that can be beneficial to the need-based learners. This paper attempts to analyze the performance of two groups of students’ persuasive speech presentations, one in the traditional mode and the other was with TV commercials to examine the impact of using TV commercials in the language classroom. This paper includes the result of a survey conducted on the students of Stamford University Bangladesh. It also discusses the limitations of using TV commercials in the context of learning EFL (English as Foreign Language)/ESL (English as Second Language), particularly in Bangladesh. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12078 Journal of NELTA, Vol 19 No. 1-2, December 2014: 32-46